Voices of the Folk: Exploring Life and Culture through Dinajpur’s Palatiya Drama Narratives (S1) (Global Journal of Human-Social Science, 2025)
Palatiya a traditional Bengali folk drama form serves as both a source of entertainment and a repository of community heritage This paper examines the life and culture of the Palatiya community through two narratives Hadangkali Biswadhagri and Dhakoshori to understand how they portray rural hardships resilience and cultural identity The study employs an interdisciplinary approach drawing on literary analysis anthropology and performance studies and uses qualitative methods with data from drama texts interviews observations photographs and relevant literature Findings show that both plays center on two women Bishobala and Dhakoshori who embody the working-class struggle against poverty and injustice while reflecting the community s traditions values and resistance to oppression These works not only preserve Bengali folk culture but also function as social documents of rural life The research contributes to folk and performance studies by highlighting Palatiya s role as a medium of cultural continuity and a voice for marginalized communities and calls for further study of ethnic cultural forms in contemporary contexts
Keywords: dinajpur; folk culture; folk drama; folk tradition; khon; palatiya; rural entertainment; cultural heritage; social protest; bengali performance arts